Reformulation Of The Arrangement Of Dzawil Arham In The Compilation Of Islamic Law To Realize Legal Certainty Of Inheritance - Mhd Nurhusein Daulay (Jurnal Sahabat ISNU SU, 2025)
This research examines the issue of inheritance law related to the status and position of dzawil arham when distributing inheritance in Indonesia.This research is presented in qualitative form. This research uses Islamic law (Islamic legal inheritance) as an analytical tool in analyzing research data. In the end, this research concludes that Decision Number: 014 / Pdt.P / 2014 /PA-LPK and Decision Number: 263 / Pdt.G / 2009 / PTA.Sby, become a legal fact that the judges of the Lubuk Pakam Religious Court and the Surabaya High Religious Court in the matter of dzawil arham determined the decision in accordance with the opinions of Ahmad bin Hambal, Imam Abu Hanifah, Ali bin Abi Thalib, Umar bin Khathab and Ibn Mas'ud. There is no explanation of the status, position and resolution of dzawil arham in full in normative jurisprudential law (Compilation of Islamic Law), so this provides an opportunity for differences of opinion and judges' decisions in the matter of dzawil arham, so it is important to provide an attachment as an additional explanation in the Compilation of Islamic Law to be a legal guideline in resolving issues concerning dzawil arham.